2005
DOI: 10.1103/physrevb.72.214204
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic versus relaxational sound damping in glasses. I. Brillouin scattering from densified silica

Abstract: This series discusses the origin of sound damping and dispersion in glasses. In particular, we address the relative importance of anharmonicity versus thermally activated relaxation. In this first article, Brillouin-scattering measurements of permanently densified silica glass are presented. It is found that in this case the results are compatible with a model in which damping and dispersion are only produced by the anharmonic coupling of the sound waves with thermally excited modes. The thermal relaxation tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 53 publications
2
39
1
Order By: Relevance
“…In the context of the experimental evidence discussed above which assumes that only the fraction of relaxing particles having lower potential barriers are involved in tunnelling local motions, the present results seem to indicate that the densification process is more efficient in depressing the local mobility of relaxing centres characterized by higher barriers than those experiencing tunnelling motion. It is worth noting that the observations resulting from this preliminary study are in agreement with recent results of Brillouin scattering measurements in a densified silica glass [21]: they showed that thermally activated relaxations become negligible after densification. A more extensive experimental and theoretical study is in progress in order to explain exhaustively the nature of the mechanisms regulating the sound propagation in densified GeO 2 glasses.…”
Section: Sound Velocitysupporting
confidence: 81%
“…In the context of the experimental evidence discussed above which assumes that only the fraction of relaxing particles having lower potential barriers are involved in tunnelling local motions, the present results seem to indicate that the densification process is more efficient in depressing the local mobility of relaxing centres characterized by higher barriers than those experiencing tunnelling motion. It is worth noting that the observations resulting from this preliminary study are in agreement with recent results of Brillouin scattering measurements in a densified silica glass [21]: they showed that thermally activated relaxations become negligible after densification. A more extensive experimental and theoretical study is in progress in order to explain exhaustively the nature of the mechanisms regulating the sound propagation in densified GeO 2 glasses.…”
Section: Sound Velocitysupporting
confidence: 81%
“…Light scattering has for a long time been used in order to investigate the atomic dynamics in disordered matter next to q = 0, where q is the wave-vector of the excitation. However, the application of highly resolving Brillouin scattering spectrometers [1], which makes it possible to determine the dispersion and the damping of the modes with high accuracy [2], has also shown quite a durable period of their development. After the development of inelastic X-ray scattering (IXS) spectrometers by the end of the last century, this technique was very successfully applied to the investigation of collective excitations in topologically disordered matter as well [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For B Ϸ 50 MHz measured at B = 0.5893 m [32], the phonon viscosity is ⌫ = 6.9ϫ 10 −7 m 2 / s. Lastly, the strength of the Bragg grating imprinted onto the waveguide, ⌬n, cannot be said to have any typical value, but can take vastly different values in different waveguides.…”
Section: Governing Equations and Physical Parametersmentioning
confidence: 99%
“…Phonon viscosity can be caused by elastic anharmonicity, Rayleigh scattering, vibrational relaxation, and impurities in the medium [32]; it scales approximately as the square of the wave number. It gives rise to damping of acoustic waves and results in a finite frequency spread for Brillouin scattering.…”
Section: Introductionmentioning
confidence: 99%